Reducing Writing Apprehension in Undergraduate Parks, Recreation, and Tourism Management Students. Issue 1 (2nd January 2023) - Stephens, Lauren E.; Kim, Gyunghoon; Fogle, E'Lisha V.; Kleinbort, Tori; Duffy, Lauren N.; Powell, Gwynn M.; Olsen, Lisa K.-P.; Kakraba Coleman, Karleisha; Gremillion, J. Paul
Abstract: The quality of undergraduate student writing is cause for concern among academics and industry professionals alike. Because writing apprehension is thought to be a contributing factor in the current deficit of undergraduate writing proficiency, the Writing Apprehension Test (WAT) was administered to parks, recreation, and tourism students to determine change in self-reported levels of writing apprehension as a result of a writing intervention program. The writing intervention program centered on the use of graduate writing mentorship and scaffolded, authentic writing assignments. Differences in pre- and post-WAT scores indicated lowered levels of writing apprehension for the intervention group. Additional analyses were conducted by deconstructing items included in the WAT into four subsets (e.g., enjoyment of writing, confident in ability, self-esteem, evaluation of writing), furthering empirical research on the WAT itself. Findings suggest that mentorship and authentic writing assignments within the discipline may be a viable avenue for improvement in undergraduate writing ability.